Sarcomatoid Carcinoma Arising in the Gallbladder of a 58-Year-Old Female: Case Report - Ahmed A. Ahmed; Yan Gao; Rossana Kazemimood (Case Reports in Hepatology, 2025)
Sarcomatoid carcinoma of the gallbladder is a rare malignancy with no specific clinical manifestation. It is characterized by the presence of malignant epithelial and mesenchymal components intermingled with each other. This disease usually presents at an advanced stage, and its final diagnosis needs to be confirmed by histopathological and immunohistochemical examination. Sarcomatoid carcinoma is characterized by early metastasis through lymphatics, rapid progression, a high recurrence rate, and a worse prognosis than usual gallbladder adenocarcinoma. Herein, we report the case of a 58-year-old female patient, who underwent laparoscopic cholecystectomy, with sarcomatoid carcinoma of the gallbladder. Histologically, the epithelial component of the tumor was composed of adenocarcinoma, and the mesenchymal component was composed of spindle cell sarcoma and chondrosarcoma. The tumor was identified as invading the perimuscular connective tissue on the hepatic side without involvement of the liver. The prognosis of sarcomatoid carcinoma of the gallbladder remains poor despite surgical resection of the gallbladder. The patient passed away in less than 1 year after the procedure despite chemotherapy due to cancer progression.